Optimising Supply Chain Management through Inventory Management Strategies: A Systematic Literature Review - Audrey Exaudina Tambunan; Ryani Virliana Muliawan; Salsabilah; Yusnaini Yusnaini (Takaza Innovatix Labs Ltd., 2026)
Supply chain management is crucial for operational efficiency amid globalization and technological advances, but faces challenges like demand uncertainty and stock imbalances from poor inventory management. This study aims to analyze inventory management strategies for optimizing supply chain performance. It uses a qualitative Systematic Literature Review (SLR) method following PRISMA guidelines. The population comprises articles from databases like Scopus, Google Scholar, and ScienceDirect; the sample includes 30 selected journal articles based on inclusion criteria such as relevance and full-text availability. Instruments involve keyword searches (e.g.,